Implementasi Peraturan Daerah Kota Medan Nomor 9 Tahun 2016 Tentang Penyelenggaraan Lalu Lintas dan Angkutan Jalan di Kota Medan - Riri Febriana; Ananda Mahardika (Universitas Muhammadiyah Sumatera Utara, 2022)
Road Traffic and Transportation is a unified system consisting of traffic, road transport, Road Traffic and Transportation networks, Road Traffic and Transportation Infrastructure, Vehicles, Drivers, Road Users, and their management. This research was conducted at the Department of Transportation of Medan City. This study aims to determine the implementation of the Medan City Regional Regulation Number 9 of 2016 concerning the Implementation of Road Traffic and Transportation in the City of Medan. The type of research used in this research is descriptive research with qualitative data analysis, namely problem-solving procedures that are examined by observation, and interviews by describing the current state of the research object based on the facts that appear or as they are. Based on the results of the study, it is known that the implementation of the Medan City Regional Regulation Number 9 of 2016 concerning the Implementation of Road Traffic and Transportation in the City of Medan has been implemented, but has not gone well enough. This is because the information is in the form of direct socialization widely on traffic regulations, and also conducts socialization about accidents that occur on the road from disorder in traffic and establishes good relationships with road users. The implementation of the disposition at the Medan City Transportation Service is by existing provisions and has been running effectively. The existing bureaucratic structure at the Medan City Transportation Service has been run by the Standard Operating Procedure (SOP).